Community Response to the Implementation of Development in Gunung Gede Village, Panggarangan District, Lebak Regency in 2024 - R, Moh Arif Mulyawan; Rohmawati, Titin (Ethics and Law Journal: Business and Notary, 2023)
This study aims to analyze community responses to the implementation of development programs in Gunung Gede Village, Panggarangan District, Lebak Regency, in 2024, and to identify the factors influencing their success. The research employed a qualitative descriptive approach with key person selection techniques. Data were collected through observation, interviews, and documentation, and validated using triangulation methods. Data analysis involved data reduction, presentation, and conclusion drawing or verification. The findings indicate that the implementation of village development in Gunung Gede has been optimal. The community responded positively, as the programs were well executed, encountered no significant obstacles, and met the residents’ needs. The success of the implementation was influenced by clear objectives, professional attitudes of implementers, strong commitment, effective communication, and community support. These results highlight the importance of collaboration between village authorities and local residents in achieving participatory and sustainable development.